L5 spondylolysis increases segmental mobility at the cranial adjacent level without altering intervertebral disc contact pressure - Ge, Zhilin; Zhao, Bingde; Xu, Xu; Chen, Lin; Liang, Dongzhu; Kang, Qingyang; Gao, Zibo; Luo, Junhua; Zhan, Jiheng; Chen, Jianquan; Zhang, Bo (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveWhile lumbar spondylolysis has been biomechanically associated with subsequent spondylolisthesis and disc degeneration, its implications on cranial adjacent segments remain unclear. This in vitro experiment aims to quantify the segmental alterations in kinematics and contact mechanics at both L5/S1 and L4/L5 levels induced by L5 pars defects.MethodsSix fresh-frozen human lumbar cadaveric specimens (L1-S2) underwent pure moment loading (4 Nm) in flexion-extension, lateral bending, and axial rotation. Sequential testing compared intact specimens with simulated L5 bilateral spondylolysis models. Intervertebral kinematics were quantified using optical motion tracking, while L4/L5 disc contact parameters were measured using Tekscan pressure sensors.ResultsL5/S1 segmental mobility increased in lateral bending (1.66°, p = 0.002) and axial rotation (1.45°, p = 0.007) in spondylolysis models. Motion increases were observed at the cranial adjacent L4/L5 segment: flexion-extension (1.89°, p < 0.001), lateral bending (2.15°, p = 0.002), and axial rotation (1.89°, p = 0.022). However, no significant differences were detected in the L4/L5 disc contact parameters for peak contact pressure, contact area, and contact force.ConclusionIsthmic defects induce segmental hypermobility at the cranial adjacent segment. This kinematic alteration may accelerate disc degeneration.